MUSCLE TISSUE: STRUCTURE, FUNCTION, BIOLOGY, AND MEDICAL SIGNIFICANCE - Qosimova Mohlaroyim Bahromjon kizi; Mukhammadjonova Dilyoraxon Khusanjon kizi (TADQIQOTLAR, 2026)
Abstract: This article provides an in-depth analysis of muscle tissue, exploring its structure, types, physiological and biochemical processes, regeneration mechanisms, and clinical relevance. It covers the development and functioning of skeletal, cardiac, and smooth muscle, assessing both their similarities and distinct features. Emphasis is placed upon the role of cellular and molecular mechanisms in muscle adaptation, maintenance, and repair, as well as on current and potential medical applications in muscle-related disease and injury.